Pacemaker and Atrioventricular Junction Ablation in Patients With Atrial Fibrillation—A Systematic Review of Systematic Review and Meta-Analysis - Zhang, Chi; Wang, Xi-Ying; Lou, Lian; Zhang, Xuan; Chen, Le-Le; Chen, Yu-Xiao; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac resynchronization therapy (CRT) could be considered for heart failure (HF) patients with atrial fibrillation (AF) unless a potent ventricular capture strategy is conducted. However, the benefit of a pacemaker (PM; as part of CRT) in patients with AF and whether atrioventricular junction (or nodal) ablation (AVAB) can improve the prognosis of these patients compared with those treated medically to support ventricular capture are unclear. Methods and Results Systematic reviews and meta-analyses investigating the roles of PMs and AVAB in patients with AF were obtained in a search of the PubMed, Embase, and Medline databases and then analyzed with respect to the following outcomes: mortality, left ventricular ejection fraction, and clinical findings including the New York Heart Association class, 6-min walk distance (6MWD), quality of life as assessed in a specific questionnaire, and response to CRT. The quality of the included reviews was assessed using the Assessing the Methodological Quality of Systematic Reviews 2 tool, which includes 16 items. This study was finally based on 13 systematic reviews or meta-analyses. The results showed that patients with AF have higher all-cause mortality rates compared with patients with sinus rhythm and that AVAB can reduce all-cause mortality in patients with AF. Although the functional improvement was better in sinus rhythm than in patients with AF, in the latter, AVAB increased the 6MWD and reduced the CRT nonresponse rate in patients with AF. Conclusion Atrial fibrillation is associated with a higher all-cause mortality rate in patients with CRT implantation. AVAB, by increasing the 6MWD and survival, can improve the prognosis of these patients.